The Knight with No Horse: Defining Nobility in Late Medieval and Early Modern Castile - Renton, Kathryn (The sixteenth century journal, 2020)
This article examines the legal relationship of horses to the status of the knight, or caballero, in late medieval and early modern Castile. Despite the upward mobility that horses offered knights serving in the Reconquest of the Iberian Peninsula, ultimately it was the reverse privilege of being exempt from service on horseback, and even the option to ride mules, that became key to claiming noble identity in late medieval Castile. In the mid-sixteenth century, non-noble knights began to underwrite claims to noble status as hidalgos through these long-standing exemptions from horse ownership, in a concrete example of social mobility at the lower edge of the noble estate. In this study, the social and legal history of the horse provides a key to new definitions of noble status in the early modern period, demonstrating both the negotiated limits of centralized power and social mobility in early modern Spain.